A Critical Discourse Analysis (CDA) of the strategic plans of Istanbul under different political administrations. Issue 1 (2nd January 2023) - İkizer, İhsan
ABSTRACT: Strategic plans are sophisticated public administration tools of local governments, which are not limited to the simple expression of priorities of a city or plans and projects to be conducted in the future. They are more than the sum of some words and expressions, and they are shaped primarily by the political approach or ideology of the administration releasing them. In this article, a comparative Critical Discourse Analysis (CDA) of the last two strategic plans of Istanbul Metropolitan Municipality (IMM) (2015–2019/2020-2024), which were prepared by mayors with different party affiliations, was conducted. It is observed that a participatory democracy discourse has been adopted in the new strategic plan with the predominant use of words such as participation, participatory, transparency, cooperation, inclusive, fair, equal, accountability etc. The rigid shift from government to governance discourse in the strategic plans of IMM is also visible in the non-linguistic practice of the municipality.